Sustainability of the Healthy Municipalities Strategy in Guatemala - Jorge Laureano-Eugenio; Raúl Otoniel Gómez-Rodríguez; Jhunny Tasejo-Corzantes; Augusto Silvestre Ramírez; Rosa María Pretell Aguilar; Jacqueline Elizabeth Alcalde-Rabanal (Pan American Health Organization, 2021)
Objective. Evaluate the sustainability of the Healthy Municipalities strategy in Guatemala in order to have solid evidence to support decision-making. Methods. A concurrent mixed-methods study was carried out in five phases: 1) theoretical-conceptual (based on a narrative review of the literature on sustainability, dimensions and categories were proposed for evaluation); 2) empirical (four municipalities were selected for convenience and 29 semi-structured interviews and four focus groups were conducted with key actors to explore sustainability; with this information, a score was assigned to each category and dimension); 3) analytical, by category and dimension (content analysis was performed for qualitative information, and totals and averages were calculated for quantitative information); 4) integrative (qualitative data were integrated into matrices by category and dimension, and quantitative data were supported by qualitative information); and 5) meta-inference (consideration was given to the context and its influence on the results). Results. Ninety-two (92) informants participated. In operational terms, progress was observed in the transfer and use of results, and in rotations in leadership. In the legal and political sphere, accountability and local planning were highlighted. In the economic sphere, progressive investment in health, water and sanitation was emphasized, as well as insufficient investment in social determinants of health. In the social sphere, few mechanisms were observed to promote and strengthen social participation. Conclusions. In the municipalities that participated in the study, a fair level of sustainability was observed in the Healthy Municipalities strategy.